From conflict to encounter: Educational paths for stopping violence, fanaticism and intolerance, Dimitriados Publishing House, Volos 2024, by V. Gogou, A. Barlou, N. Tsirevelou, & Ch. Fradellou. - Syrgianni, Maria (Greek Journal of Religious Education (GjRE), 2024)
Book review: From conflict to encounter: Educational paths for stopping violence, fanaticism and intolerance, Dimitriados Publishing House, Volos 2024, by V. Gogou, A. Barlou, N. Tsirevelou, & Ch. Fradellou.